Respuesta :

Answer:

4

Step-by-step explanation:

Answer:

x = 2 y = -1 or (2,-1)

Step-by-step explanation:

-2x + y= -5

Moved -2x to the other side

y = 2x - 5

2y + 3x = 4

Substitute y with 2x - 5

2(2x - 5) + 3x = 4

Distribute

4x - 10 + 3x = 4

Combine the terms

7x - 10 = 4

Move the constant to the other side

7x - 10 = 4

    +10  +10

7x = 14

Divide both side by 7

7x/7 = 14/7

x = 2

Back to -2x + y= -5

Substitute the x with 2

-2(2) + y = -5

Combine the terms

-4 + y = -5

Move the constant to the other side

-4 + y = -5

+4        +4

y = -1